2008
DOI: 10.1021/ac702367m
|View full text |Cite
|
Sign up to set email alerts
|

Fast Electrophoretic Separation Optimization Using Gradient Micro Free-Flow Electrophoresis

Abstract: The continuous nature of micro free-flow electrophoresis (μ-FFE) was used to monitor the effect of a gradient of buffer conditions on the separation. This unique application has great potential for fast optimization of separation conditions and estimation of equilibrium constants. COMSOL was used to model pressure profiles in the development of a new μ-FFE design that allowed even application of a buffer gradient across the separation channel. The new design was fabricated in an all glass device using our prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 29 publications
0
61
0
Order By: Relevance
“…In 2006-2010, Bowser and coworkers conducted a series of fundamental studies on the flow controlling [24], band and resolution optimizations [25], mitochondria mobility determination [26], and aptamer equilibria measurement [27]. A lot of works have demonstrated that C-FFE could be excellently used for the analyses of mitochondria [26], aptamers [27], and proteins [28] as well as the estimation of equilibrium constants [29]. Nonetheless, few of the works were reported on the micropreparation of biosample via C-FFE.…”
Section: Introductionmentioning
confidence: 99%
“…In 2006-2010, Bowser and coworkers conducted a series of fundamental studies on the flow controlling [24], band and resolution optimizations [25], mitochondria mobility determination [26], and aptamer equilibria measurement [27]. A lot of works have demonstrated that C-FFE could be excellently used for the analyses of mitochondria [26], aptamers [27], and proteins [28] as well as the estimation of equilibrium constants [29]. Nonetheless, few of the works were reported on the micropreparation of biosample via C-FFE.…”
Section: Introductionmentioning
confidence: 99%
“…The Bowser group from the University of Minnesota has made several contributions to FFE since 2008 [10][11][12]22]. In one study, Fonslow and Bowser used a microchip with varying depths to study the effects of a buffer concentration gradient on separations [10] and in another study, to separate mitochondria [11].…”
Section: Ffementioning
confidence: 99%
“…In one study, Fonslow and Bowser used a microchip with varying depths to study the effects of a buffer concentration gradient on separations [10] and in another study, to separate mitochondria [11]. In the first article, a concentration gradient in cyclodextrin was created, and the effect on amino acid separation was examined, as well as an efficient determination of the ideal separation conditions [10].…”
Section: Ffementioning
confidence: 99%
See 1 more Smart Citation
“…Free flow electrophoresis is a continuous separation technique that utilizes hydrodynamic flow and an applied electric field perpendicular to the flow to separate analytes in flowing streams (54). Recent developments of this method include studies by Bowser and co-workers on the use of free flow electrophoresis in the separation of mitochondria and primary amines (56)(57)(58). Zalewski et al demonstrated synchronized, continuous flow zone electrophoresis on a microfluidic device for the first time (59).…”
Section: Protein Profilingmentioning
confidence: 99%